Men, masculinities and violence against non-human animals: towards an intersectional approach - Aavik, Kadri (Interconnecting the violences of men, 2025)
This chapter explores some key ways in which violence against non-human animals is structural, institutional, intersectional and linked to men and masculinities. It examines the deeper underlying logic and processes, which make violence against non-human animals possible, and traces common origins behind different kinds of violences. It is discussed how men’s violence against non-human animals is interconnected with their violence towards marginalised humans. The chapter argues that our understanding of violence – including what counts as violence – is informed by hierarchical relations between beings, constructed and perpetuated according to masculine logic and benefitting elite men first and foremost. It is suggested that reducing violence towards non-human animals is impossible without ending their status as objects of consumption. Also, non-human animal oppression cannot be contested without dismantling – both discursively and materially – sexism and gender-based hierarchies, ableism, racism, colonial legacies and other oppressive systems. To challenge these interconnected violences and break links between men, masculinities and violence against non-human animals, urgent changes are needed in ideals of masculinity and in the practices of men.